DATA PROCESSING OF MAGNETOTELLURIC METHOD USING CONTINUOUS MORLET WAVELET TRANSFORM METHOD - SYAHWANTI (NIM : 20215022), HEZLIANA
Data processing Magnetotellurik method using Fourier transform has been done. Fourier transforms that have been used to have a sense of the magnetotellurik raw data are represented only in the form of frequency only while the raw data MT method has changes to time and frequency. So it takes transformation that can represent data in time domain and frequency domain. The use of Continuous Morlet Wavelet Continuous Transformation Method in this study aims to represent data of magnetotellurik method in time-frequency domain. So we can see the variation of electric field data and magnetic field in time-frequency domain. After that the data will be filtered to minimize noise on the data. Then will be calculated impedance value and apparent resistivity and phase in this research data. The impedance (Zxy and Zyx), the apparent resistivity (Rhoxy and Rhoyx) and phase (Phasexy and Phaseyx) generated in this study have a more consistent graphic value than the value generated by the Phoenix software. In addition, at low frequencies the error bar values generated in this study are smaller than the software results.